Group Dynamics and Allocation of Advanced Heart Failure Therapies—Heart Transplants and Ventricular Assist Devices—By Gender, Racial, and Ethnic Group - Khadijah Breathett; Ryan Yee; Natalie Pool; Megan C. Thomas Hebdon; Shannon M. Knapp; Kathryn Herrera‐Theut; Esther de Groot; Erika Yee; Larry A. Allen; Ayesha Hasan; JoAnn Lindenfeld; Elizabeth Calhoun; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background US regulatory framework for advanced heart failure therapies (AHFT), ventricular assist devices, and heart transplants, delegate eligibility decisions to multidisciplinary groups at the center level. The subjective nature of decision‐making is at risk for racial, ethnic, and gender bias. We sought to determine how group dynamics impact allocation decision‐making by patient gender, racial, and ethnic group. Methods and Results We performed a mixed‐methods study among 4 AHFT centers. For ≈ 1 month, AHFT meetings were audio recorded. Meeting transcripts were evaluated for group function scores using de Groot Critically Reflective Diagnoses protocol (metrics: challenging groupthink, critical opinion sharing, openness to mistakes, asking/giving feedback, and experimentation; scoring: 1 to 4 [high to low quality]). The relationship between summed group function scores and AHFT allocation was assessed via hierarchical logistic regression with patients nested within meetings nested within centers, and interaction effects of group function score with gender and race, adjusting for patient age and comorbidities. Among 87 patients (24% women, 66% White race) evaluated for AHFT, 57% of women, 38% of men, 44% of White race, and 40% of patients of color were allocated to AHFT. The interaction between group function score and allocation by patient gender was statistically significant (P=0.035); as group function scores improved, the probability of AHFT allocation increased for women and decreased for men, a pattern that was similar irrespective of racial and ethnic groups. Conclusions Women evaluated for AHFT were more likely to receive AHFT when group decision‐making processes were of higher quality. Further investigation is needed to promote routine high‐quality group decision‐making and reduce known disparities in AHFT allocation.